Foundation of a millenary civilization: Egypt and the origin of mathematical measurement systems - Zárate , Idaldo Abdiel Atencio; Ruíz , Narciso Galástica; Medina , Alcibiades (Seven Editora, 2024)
The ancient civilization of Egypt left a significant mark on the evolution of mathematical concepts, which is of great importance due to its influence in this field. The ancient Egyptian mathematicians set important precedents in modern mathematics through their innovative approach to solving practical problems that for their time must have been of a high level of complexity.In ancient Egypt, applications were based on the decimal system and mathematical techniques were fundamental in their day-to-day life. The Egyptian numeral system, which used multiples of ten and hieroglyphics, offered an efficient way to perform mathematical operations and manage resources. This non-positional approach, in which the value of a symbol did not depend on its position in the number, allowed the Egyptians to perform complex tasks related to accounting, architecture, and astronomy.One of the main characteristics of Egyptian mathematics was its use in everyday life. In administrative management, notaries employed the ten-number system to record assets and taxes on papyrus documents, simplifying resource management and accounting. In the planning and construction of monuments such as the pyramids, Egyptian mathematics was instrumental as precise calculations were needed to measure and calculate proportions. In addition, the decimal system was used in astronomy for the tracking of astronomical cycles and the elaboration of calendars, which was essential for agriculture and religious structure.Egypt's mathematical heritage not only had an impact on contemporary mathematical practice, but also developed the foundation for future advances in this discipline. Despite being non-positional, the Egyptian numeral system, with its base 10 and methods of calculation, impacted later numerical systems and the advancement of Greek and current mathematics. Research of Egyptian mathematical papyri, such as the Rhind Papyrus, reveals how. DOI:https://doi.org/10.56238/sevened2024.026-012